K26 Specific in-patient rehabilitation improves postural and gait instability in huntington's disease. (13th September 2016) - Brabcová, Libuše; Roth, Jan; Ulmanová, Olga; Horáček, Ondřej; Kolářová, Milena; Božková, Helena; Rusz, Jan; Košková, Pavla; Lísalová, Kateřina; Jančok, Filip; Klempíř, Jiří; Růžička, Evžen; et al.
Abstract : Background: Huntington's disease (HD) is an untreatable hereditary neurodegenerative disease manifesting various types of motor disorders including stability and gait disturbances, together with cognitive and behavioural impairments. The symptomatic therapy is limited and temporary. Rehabilitation (Rhb) is considered to be beneficial in postural and gait instability treatment and prevention of falls. However, there is very limited evidence-based information on the Rhb therapy effects and no specific Rhb management. Aims: To evaluate long-term effects of targeted rehabilitation on postural and gait stability in the early and middle stages of HD. Methods: 8 genetically verified HD patients in the early and middle stages, without severe cognitive deficit (Mini Mental State Examination >20) and without depression (Beck Depression Inventory 0–9) were examined at the baseline using UHDRS (Unified Huntington's Disease Rating Scale), gait stability examination (Dynamic Gait Index-DGI), posturography (Limits of Stability; LOS-static, dynamic), Falls Efficacy Scale-FES (fall risk) and Clinical Global Impression-CGI (subjective effect of treatment evaluation) questionnaires. Then they underwent a 3-week inpatient rehabilitation program including: A. individual physiotherapy focused on gait, stability and coordination, twice a day 30 min., B. 60 min of condition training, C. 30 min of occupational therapy. The follow-up testing with the same battery was realised immediately, 1 month and 3 months after completion of the rehabilitation programme. Results: There was a statistically significant improvement in DGI (p < 0.001) in all intervals compared to the baseline and in LOS-static (p = 0.003) in all intervals compared to the baseline. No improvement was found in UHDRS and questionnaires (FES, CGI). Conclusions: Specific rehabilitation methods improve the postural and gait stability in patients with HD. The effect persists at least for 3 months. With the support of: GAUK 1888214, IGA NT 11190–6/2010 and PRVOUK P26/LF1/.